Detection of early neoplasia in Barrett's esophagus using lectin-based near-infrared imaging: an ex vivo study on human tissue. - Neves, André A.; Di Pietro, Massimiliano; Brindle, Kevin M.; Waterhouse, Dale J.; Bohndiek, Sarah E.; O'Donovan, Maria; Fitzgerald, Rebecca C. (Endoscopy, 2018)
Background and Study Aims: Endoscopic surveillance for Barrett's esophagus (BE) is limited by long procedure times and sampling error. Near-infrared (NIR) fluorescence imaging minimizes tissue autofluorescence and optical scattering. We assessed the feasibility of a topically applied NIR dye-labeled lectin for the detection of early neoplasia in BE in an ex vivo setting.Methods: Consecutive patients undergoing endoscopic mucosal resection (EMR) for BE-related early neoplasia were recruited. Freshly collected EMR specimens were sprayed at the bedside with fluorescent lectin and then imaged. Punch biopsies were collected from each EMR under NIR light guidance. We compared the fluorescence intensity from dysplastic and nondysplastic areas within EMRs and from punch biopsies with different histological grades.Results: 29 EMR specimens were included from 17 patients. A significantly lower fluorescence was found for dysplastic regions across whole EMR specimens (P < 0.001). We found a 41 % reduction in the fluorescence of dysplastic compared to nondysplastic punch biopsies (P < 0.001), with a sensitivity and specificity for dysplasia detection of 80 % and 82.9 %, respectively.Conclusion: Lectin-based NIR imaging can differentiate dysplastic from nondysplastic Barrett's mucosa ex vivo.